Advances in the study of HLA class Ib in maternal-fetal immune tolerance - Yang, Yiran; Wang, Wanning; Weng, Jing; Li, Huifang; Ma, Yanmin; Liu, Lingyan; Ma, Wei (Frontiers in Immunology, 2022)
The HLA class Ib molecule is an alloantigen that causes transplant rejection on behalf of individual human and plays an important role in maternal-fetal immune tolerance. Early studies on HLA class Ib focused on the mechanism of HLA-G-induced immune escape, but in recent years, studies on the mechanism of HLA-G have deepened and gradually explored the mechanism of HLA-E and HLA-F, which are also HLA class Ib molecules. In the maternal-fetal interface, trophoblast cells express HLA class Ib molecules to protect the fetus from maternal immune cells by binding to inhibitory receptors of decidual immune cells (DICs) and shifting Th1/Th2 balance toward Th2 bias. Covering the latest research, this review systematically demonstrated the molecular mechanism of HLA class Ib, and provides a reference for its application in the field of clinical assisted reproduction.